Fabrication of a carbon-based immuno-biosensor for hepatitis B surface antigen detection - Willy Wong, Xiu Fa (2014)
Since the early diagnosis of HBV infection is crucial for the successful antiviral treatment, sensitive methods are urgently needed for measuring bio-diagnosis markers present at ultra-low levels during early stages of the infection. In this proposal, a graphene based biosensor is presented for performing highly sensitive pathogenic virus detection, particularly toward the detection of Hepatitis B virus surface antigen (HBsAg). A free standing conductive graphene will be prepared using a modified Hummers method. Graphite will be oxidized to graphene oxide which will then be reduced to graphene by using hydrazine as the reducing agent. The product before and alter hydrazine reduction was tested with UV-Vis spectrometer to obtain the peak at certain wavelength. Before reduction, the peak was shown around 230-240 nm while after reduction, the peak was around 270 rim. The peak shift from 230 nm to 270 nm shows that the synthesis of graphene was successful. The final product of the reduction was a black color powder. The immobilization of the antibody will be done using this graphene as substratum. The graphene is used to grow the Nafion- and was then soak in Thionine solution. Following that, a solution of primary antibodies against hepatitis B surface antigen (anti-HBsAg IgG) was incubated on the biosensor. After the immobilization, the antigen was dropped onto the biosensor, follow by incubation of secondary antibodies conjugated to Horseradish Peroxidase (HRP). The color change to blue upon addition of Tetramethylbenzidine (TMB). Sulfuric acid stop solution was then added and colour changes from blue to yellow was observed. This colour change indicate that the immobilization of anti-HB sAg on the graphene surface was successful.